KARAKTERISTIK REKAHAN BATUBARA PADA EKSPLORASI GAS METANA BATUBARA DI CEKUNGAN OMBILIN, SUMATRA BARAT - Abdurachman Ibrahim, Muhammad
Exploration of coal bed methane (CBM) which is one of alternative energy, currently being supported by the government of Indonesia to diversify national energy. Indonesian coal characteristics are very different because of its Tertiary age, making the exploration of coalbed methane in Indonesia has its own characteristics. One characteristic that can be observed is the fracture of coal (cleats). Microcleat analysis is used to view the appearance of maceral, minerals, cleat aperture, and cleat spacing. Microcleat analysis also shows the porosity and permeability, as well as gas content, based on physical characteristics of cleat aperture and spacing. The research method includes field study and data processing. Field study is used to obtain drilling and outcrop data. The data from drilling consist of core samples, well log, and gas data. The outcrops data consist of strike and dip from cleat and coal seam. Data processing is used to analyze microcleat, maceral compositions, porosity, permeability, gas adsorption, and cleat structure analysis. The research area located at Sawahlunto, West Sumatra Province. Geographically is located between coordinates 0°36'00"-0°42'00" latitude and 100°45'00"-100°48'00" longitude. This area is included in the Ombilin Basin, with three rock intervals, consisting of Sawahlunto Formation, Rasau members of Sawahtambang Formation, and Sawahtambang Formation. The coal bed methane drilling reached 451 meters, penetrated Sawahlunto Formation as a coal carrier formation deposited in the delta environment. There are five layers of coal, comprising of layers A, B, C, D, and E. Vitrinite reflectance in the study area ranged from 0.66 to 0.80%, and the calorific value from 7434-7646 Cal/gr. Coal rank based on American standards classification (ASTM) included in the high-volatile bituminous. Vitrinite is dominated maceral group, with a percentage more than 90%. Based on microcleat analysis, narrow aperture, discontinuous, mineral filled, wide spacing, and a few number of cleats, will give a poor permeability. Conversely, wide aperture, without mineral filled, close spacing, and a lot of cleats, will provide a good permeability. Microcleat analysis shows that the deeper coal will decrease cleat aperture, so that permeability will be decline. High porosity is obtained from a large pore diameter, wide aperture, and closer spacing of cleats. Microcleat analysis proved that the permeability is not very much influence the gas content. However, microcleat which physically demonstrates the wide aperture, continuous, and without minerals filled will give good gas content. Gas content will also be better when the aperture is narrow, the number of cleats is abundant, and cleats spacing are close. Wide aperture whose distribution is local and discontinuous will tend to have bad gas content. Face cleat trend on the study area is northwest - southeast and north – south. Direction of coal cleat can be used to determine the optimum drilling and horizontal drilling. The best direction is perpendicular to the direction of face cleats.